Promosi Dan Informasi Pada Media Komunikasi Visual Berbentuk Majalah Coconut Island Carita Banten - Desy Apriani; Wahyu Hidayat; Rizkha Ayu Apri Hapsari Gunawan (UNIVERSITAS RAHARJA, 2019)
Information into the various aspects of life, with this reason attention to process. Coconut Island Carita Banten need media design information magazine and promotions to promote the Coconut Island Carita Banten to the wider community especially the locals and tourists outside the premises. On the concept of there stages of rough layouts, konferehensip layouts, layout so. In order to produce a draft of the media-based design magazine information and the promotion of good quality and used applications supporting adobe photoshop